Polyoxometalate clusters: inorganic ligands for functional materials - Dey, Chandan (Journal of Cluster Science, 2022)
Research in polyoxometalates (POMs) is a diverse growing field with variations in application. POMs are consisting of metal ion and oxide. Peripheral oxides of POM can share spare electron pairs to behave as ligands. This property of POM was utilized for constructing coordination polymers (CPs), synthesizing transitional metal substituted POM for catalysis, synthesizing and stabilizing nano-particles, etc. POM connected structures have provided an opportunity of heterogenization of some homogeneous POM catalyst. Furthermore, diamagnetic POM ligands have been suitable for stabilizing and isolating magnetic ions inside clusters. The scope of this review is to summarize the role of POMs as ligands to prepare POM based CPs, synthesize and stabilize metal nano-particles and isolate magnetic ion or unit.
Keywords: Coordination polymer; Inorganic ligand; materials science; polyoxometalates; synthesis design